Visual outcomes of cataract surgery in adult patients with hyperopia and amblyopia with the dominant vs amblyopic eye operated on first (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To review the impact of the surgical eye sequence (dominant vs non-dominant first) on the visual outcomes of phacoemulsification with IOL implantation in patients with hyperopia and amblyopia.Material and Methods: We retrospectively reviewed the clinical outcomes of 40 adult patients (80 eyes) with hyperopia and amblyopia who underwent surgery for cataract. Group 1 comprised 28 patients (56 eyes) in whom the amblyopic eye was operated on first. This group was subdivided into two subgroups. Subgroup 1A comprised 17 patients (34 eyes) with a baseline interocular best-corrected visual acuity (BCVA) difference of not more than 0.1. Subgroup 1B comprised 11 patients (22 eyes) with a baseline interocular BCVA difference of more than 0.1. Group 2 comprised 12 patients (24 eyes) in whom the dominant eye was operated on first and the amblyopic eye was operated second.Results: After surgery, BCVA increased from 0.25 ± 0.08 to 0.76 ± 0.13 (Р ≤ 0.00001) in group 1A and from 0.33 ± 0.09 to 0.54 ± 0.07 (Р = 0.00007) in group 1B, and hardly changed in group 2 (from 0.32 ± 0.07 to 0.33 ± 0.06, Р = 0.0678). A cumulative uncorrected visual acuity (UCVA) of 0.7 or better was achieved in 67% of patients in group 1A; 0.5-0.6 was achieved in 68% of patients in group 1B; and 0.3-0.4 was achieved in 96% of patients in group 2. A cumulative BCVA of 0.7 or better was seen in 77% of patients in group 1A; 0.5-0.6 was seen in 86% of patients in group 1B; and 0.3-0.4 was seen in 92% of patients in group 2.Conclusion: The surgical eye sequence is critical in cataract surgery: operating on the amblyopic eye first creates the preconditions for its more active involvement in the visual process, which improves the chances for functional rehabilitation, especially in the presence of a small baseline interocular difference in visual acuity.
Keywords: cataract; phacoemulsification; adults; hyperopia; amblyopia; visual acuity; amblyopic eye; dominant eye